Development of a Biotechnology Innovation Handout Based on Research on the Ratio of Butterfly Pea Flower (Clitoria ternatea L.) Tea, Aquafaba, and Fermentation Duration on Lactic Acid Levels in Calpis Beverages for Grade XII High School Biology Learning - Febriyana Dwimas Praarafati (Studia : Journal of Humanities and Education Studies, 2025)
This study aimed to develop a biotechnology innovation handout for Grade XII biology learning, based on experimental research investigating the effects of butterfly pea flower (Clitoria ternatea L.) tea ratio, aquafaba addition, and fermentation duration on lactic acid levels in Calpis-like beverages. The research employed an experimental design using factorial treatments with varying tea–aquafaba ratios (1:0 to 3:1) and fermentation times (0, 24, 48, and 72 hours), inoculated with Lactobacillus acidophilus FNCC 0051. Lactic acid levels were measured by titration, supported by pH observations, color changes, and sensory evaluations. Results showed that lactic acid concentration increased from 0.00150% at 0 hours to a peak of 0.00240% at 48 hours, before declining at 72 hours. The 1:1 tea aquafaba ratio produced the most balanced acidity, stable color, and favorable sensory properties. These findings were then integrated into a handout designed according to the 5E instructional model. Expert validation rated the handout “very feasible” with an overall score of 89.5%. The study concludes that research-based handouts can effectively contextualize biotechnology, improve student engagement, and foster scientific literacy while promoting local food innovation.